Engaged and/or enraged: The perils of ‘innovative’ digital engagement around health issues - Wolf, Katharina; Archer, C.; Kao, K. (Deakin University Australia, 2017)
On May 21, 2015, The Guardian newspaper reported that TEDxSydney had designed a new national campaign to change social attitudes towards people living with disabilities (Davey, 2015). The campaign, announced at the Sydney Opera House, was due to be launched in December 2015 to coincide with the United Nations International Day of People with Disability and was framed as being in memory of Stella Young, a writer, comedian and disability advocate, who died in December 2014. Arguably it was an innovative campaign, with the potential to put disabilities on the social media map. As with many social campaigns at the time, the initiative was primarily built around a hashtag (#StellasChallenge) and sought to engage with both the disabled and the non-disabled. While the objective of the exercise was framed as “changing social attitudes”, the subsequent engagement between the organisation, TEDxSydney, and representatives of the disabled community was arguably not what TEDxSydney had intended. Ironically, the campaign was said to be inspired by Stella, who had proclaimed that she despised “inspiration porn” related to those with disabilities (Davey, 2015). Using a case study approach methodology, this paper provides an analysis of #StellasChallenge to develop an in-depth understanding of what innovative engagement does - and importantly does not - mean in the digital public sphere, through the broad lens of health at the community, organisational and individual levels of society. The paper highlights the challenges inherent in the digital world when attempting to innovatively engage with publics on sensitive, complex and deeply personal issues, such as disability and more broadly health. It draws on theory and practice in digital advocacy, public relations, web communication, health communication, issues management and stakeholder and community engagement. In the spirit of innovation (the theme of the 2016 PRIA national conference and research symposium where an early version of this paper was presented), this paper includes first-hand insights and critical reflections by one of the activists who campaigned against the #StellasChallenge initiative.